2007
DOI: 10.1055/s-2007-970049
|View full text |Cite
|
Sign up to set email alerts
|

Local Treatment of Ectopic Pregnancy

Abstract: The treatment of ectopic pregnancies has evolved from a purely surgical route with routine removal of the fallopian tube to one with multiple options. Medical treatment can be administered systemically or via local injection. Local delivery of chemotherapeutic agents is a safe and proven modality that is especially indicated for pregnancies in which a laparoscopic approach is not ideal and systemic therapy either has failed or is not desired. Local therapy has the potential to document immediately the cessatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
(94 reference statements)
0
12
0
1
Order By: Relevance
“…Administration can be undertaken with either ultrasound or laparoscopic guidance. Even though there are a handful of reports showing the effectiveness of local injection of MTX on ectopic pregnancy, not only as first-line treatment but also as a rescue method (15,16), there is still uncertainty regarding the agent for local injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration can be undertaken with either ultrasound or laparoscopic guidance. Even though there are a handful of reports showing the effectiveness of local injection of MTX on ectopic pregnancy, not only as first-line treatment but also as a rescue method (15,16), there is still uncertainty regarding the agent for local injection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the best regimen for use with local injection is still uncertain (6), although MTX is the most widely used and readily available (7). In our previous reports (8-10), we found that etoposide, an antineoplastic agent that can produce cytotoxic effects by damaging DNA, thereby inhibiting or altering DNA synthesis, is a potential candidate drug for the management of ectopic pregnancy.…”
Section: Injection Methotrexatementioning
confidence: 99%
“…[3,10] Lokal tedavi yeterli olmadığında sistemik metotreksat tedavisi veya cerrahi uygulanabilir. Biz olgumuzda ilk etapta sistemik metotreksat uygulamayı düşünsek de, hastada akut batın bulgularının gelişmesi nedeniyle cerrahi kararı verilmiştir.…”
Section: Discussionunclassified
“…Many different agents have been used to treat ectopic pregnancies including systemic and local methotrexate, local potassium chloride and hyperosmolar glucose, prostaglandins, danazol, etoposide, and mifepristone [3]. Most investigators have reported varying success rates in the medical treatment of abdominal pregnancies with local potassium chloride and/or local methotrexate, sometimes with the addition of systemic methotrexate [4].…”
Section: Discussionmentioning
confidence: 99%